Peran Media dan Sumber Belajar dalam Meningkatkan Efektivitas Pembelajaran - Khikmatul Fajriyah; Riska Nur Amalia; Riza Faishol (Jurnal Wahana Literasi Pendidikan, 2026)
This study aims to comprehensively analyze the role of instructional media and learning resources in enhancing learning effectiveness through a systematic literature review. The research was motivated by the need for an integrative conceptual model that synergizes the two elements holistically, as most previous studies in Indonesia still examined them separately. Using a qualitative approach with library research methods, data were collected from scientific documents published in the last ten years (2015-2025) through Google Scholar, Garuda Portal, and SINTA. Data analysis was conducted using qualitative content analysis with the stages of data reduction, data display, and conclusion drawing/verification. The findings indicate that media and learning resources have complementary roles: media acts as a mediating system that bridges abstract ideas, while learning resources serve as the content and context that provide substance and meaning. Three dominant synergy patterns were identified: amplification-concretization, contextualization-authenticity, and collaboration-construction, each contributing to cognitive, affective, and psychomotor aspects. As a novelty, this study formulates an integrative conceptual framework called the Synergistic Design Cycle (SIDES), which emphasizes strategic matching between media and learning resources in a cyclical, reflective process. This framework is intended as a practical guide for educators and curriculum developers to design more effective, efficient, and relevant learning experiences in the digital era.